Classification-Based Approaches to Myopia Control in a Taiwanese Cohort - Hsieh, Meng-Wei; Chang, Hsu-Chieh; Chen, Yi-Hao; Chien, Ke-Hung (Frontiers in Medicine, 2022)
Purpose: Myopia is a disorder of growing prevalence in school-aged children worldwide, especially in Asia. Although low-dose atropine is recognized as an effective treatment to slow myopia progression, different studies have reported varying efficacies of treatment, and the optimal concentration of low-dose atropine remains an open question. Methods: A two-stage approach was conducted in this study. First, an observational study was conducted to plot the axial length growth curve for Taiwanese children. Second, an interventional two-year study was performed in which different concentrations of low-dose atropine were applied based upon the risk-level status from the first stage. Results: A total of 4091 subjects, consisting of 2105 boys (51.5%) and 1986 girls (48.5%), were enrolled in the first stage to plot the axial growth curve for Taiwanese children aged between 3 and 16 years. The percentage of children with myopia increased from 2.3% in 4-year-olds to 88.0% in 16-year-olds. At the second stage, a total of 886 subjects (307 (34.65%) at low risk, 358 (40.41%) at moderate risk and 221 (24.94%) at high risk) were enrolled to receive low-dose atropine based upon the risk level (0.02%, 0.03% and 0.05%, respectively). With this approach, the mean annual myopia progression was -0.33 D, -0.57 D and -0.82 D in the low-risk, moderate-risk and high-risk groups, respectively. Applying annual myopic progression less than -1.0 D as a criterion for responder, the responder rates were 95.77%, 83.52% and 70.59% in the low-risk, moderate-risk and high-risk groups, respectively. Conclusions: We proposed a classification-based approach involving different concentrations of low-dose atropine based upon an individual’s risk-level status. With this approach, myopic progression can be effectively controlled in patients without exposure to atropine side effects due to exposure to a higher dose than actually needed.